(untitled) (Indian Journal of Arid Horticulture, 2013)
The experiment was conducted on seven and eight years old trees of NA-7 aonla to evaluate the influence of various levels of organic (FYM, biofertilizers) and inorganic (NPK) sources of nutrients on morphometrix, productivity and quality attributes of aonla and soil quality during 2009-10 and 2010-11 under hot semi-arid ecosystem. Significant improvement was recorded in soil quality by application of different combinations of N P K, FYM and biofertlizers. The vegetative growth and soil quality were influenced significantly by different sources of nutrients. Maximum vegetative growth was recorded in the plants which were applied with standard doses of N P K which was closely followed by Farm Yard manure plus 50% of the standard dose NPK. The soil properties in terms of pH, EC showed declining trend whereas level of hydraulic conductivity, organic carbon increased with the application of various combinations of FYM and biofertilizers, whereas pH, EC, hydraulic conductivity, bulk density and organic carbon of the basin soil applied with standard dose of NPK were not improved considerably.